IMPLEMENTASI PENDAFTARAN TANAH SECARA SISTEMATIK BERDASARKAN PERATURAN MENTERI AGRARIA DAN TATA RUANG/KEPALA BADAN PERTANAHAN NASIONAL REPUBLIK INDONESIA NOMOR 6 TAHUN 2018 TENTANG PERCEPATAN PENDAFTARAN TANAH SISTEMATIS LENGKAP - FADHOLI, MUHAMMAD (Dinamika Hukum, 2018)
The purpose of this study is to: 1) Review and analyse the implementation of the registration of property rights over land are systematically complete with the enactment of the Ordinance of the Minister of Agrarian Affairs and Spatial/head of the national land Agency of the Republic of Indonesia number 6 Year 2018 of Systematic Land Registration Full Acceleration. 2) examines the obstacles that occur in the implementation of the registration of property rights over land are systematically complete national land Agency Office on Boyolali Regency.The method of approach in writing this is the juridical sociological. The specification of this research uses descriptive analytic. Data source use the primary data and the data of skunder. Engineering data collection using the study interview, the library and study the documents. To analyze the data, the researchers used a qualitative descriptive methods of analysis.Based on the research results obtained conclusions that: 1) the implementation of a systematic Land registration is complete (PTSL) is one of the Government's activities in the field of land registry in the form of pensertifikatan in bulk in order to help the entire the economic classes, especially medium and low economy. PTSL program will be held regularly every year, where most of the sources of the Fund are borne by the Government, as well as the stages in the implementation of PTSL in Boyolali Regency can already run well and have been implemented in accordance with the applicable provisions in the Ordinance of the Minister of Agrarian Affairs and Spatial/head of the national land Agency of the Republic of Indonesia number 6 Year 2018 of Systematic Land Registration Full Acceleration ... This success rate is indicated through the implementation period of only 5 months of work from 1 year budget work, as well as the publication of 80% certificate of land that PTSL enrolled in the program. 2) factors that become an obstacle in the implementation of PTSL in Boyolali Regency, among others: (a) the level of education of a society that is still very low, causing not all components of the community understands and has rapid response resource related PTSL's implementation. (b) the applicant has difficulty to PTSL was presented at the time of measurement activities because of some of the bustle. (c) the applicant does not perform the installation of the sign limits with some reason, either because there has been no precise time or still going to dispute with the owner of the land that borders this caused delays in implementation activities. (d) the completeness of the collection of administrative terms by the applicant. Keywords: Land Registry, Systematic, Complete.